Reprogramming the host: Mycobacterium tuberculosis as a silent architect of the immuno-tumoral - Chávez-Domínguez, Rodolfo L.; Torres, Martha; Acevedo-Domínguez, Atziri A.; Ibarra-Inocente, Jesús A.; Carranza, Claudia (Frontiers in Cellular and Infection Microbiology, 2025)
Pulmonary tuberculosis, caused by Mycobacterium tuberculosis (Mtb), remains one of the leading causes of infectious disease-related mortality worldwide. In parallel, lung cancer represents the most lethal neoplasm, with high mortality rates globally. Emerging studies suggest that chronic Mtb infection may contribute to the development of lung cancer, particularly adenocarcinoma. Several biological mechanisms support this hypothesis. Chronic inflammation from tuberculosis creates a microenvironment enriched in proinflammatory cytokines, reactive oxygen species (ROS), and growth factors that favor cell proliferation, genomic instability, angiogenesis, and immune evasion, which are considered classic hallmarks of cancer. Additionally, both protein and non-protein virulence factors of Mtb have been shown to interfere with critical cellular signaling pathways related to tumor cell survival and invasion. Clinically, multiple observational studies and meta-analyses report an increased incidence of lung cancer among individuals with a history of tuberculosis, especially when both conditions coexist in the same pulmonary regions. Specific mutations, including EGFR, have been identified in patients with prior tuberculosis, influencing both prognosis and therapeutic response. Nevertheless, key questions remain regarding the causal nature of this association, the role of Mtb strains, and the molecular factors such as epigenetic modifications or the lung microbiome. This review proposes that infection with Mtb could function as a carcinogenic agent. Further in vitro experiments, cellular models, and clinical investigations are urgently needed to support potential reclassification of this pathogen by international agencies such as the IARC.